Model Pengembangan Agribisnis Bawang merah di Kabupaten Majalengka - Andayani, Sri Ayu (JURNAL AGRIUST, 2025)
This study aims to determine: (1) the net income of shallot farming/ha/MT, (2) the feasibility of shallot farming, and (3) the strategy for shallot farming. This study was conducted using purposive sampling. The sample was randomly selected using the Slovin formula with a sample size of 32 families. The primary and secondary data used in this study were primary and secondary data. The results showed that the average net income of shallot farming was Rp. 17,352,288.10/ha/MT. The feasibility of the farming business was indicated by the R/C value of 2.03, which means this farming business is worth continuing. Suggested development strategies include the use of farmer groups and the application of agricultural technology to increase productivity. This research is expected to provide a positive contribution to farmers in increasing income and the sustainability of shallot farming in the area.